Estimating gestational age and its relation to the anthropometric status of newborns: a study comparing the Capurro and ultrasound methods with last menstrual period - Nunes,Maria de Fátima Pussick (2011)
OBJECTIVE: to assess the accuracy of the Capurro somatic and ultrasound methods, taking date of last menstruation as a reference point, for evaluating gestational age and anthropometric classification of term newborns. METHODS: a prevalence study was carried out involving 309 pregnant women and their term newborns, 92 of whom were small for gestational age and 217 appropriate sized for gestational age, at two public maternity hospitals in the Brazilian city of Salvador. The evaluation of the differences between the median gestational age according to the two methods was carried out using the non-parametric "Wilcoxon Signed-Rank Test." The accuracy of the methods for evaluating gestational age for the small for gestational age newborns was estimated by calculating the sensitivity, specificity, positive predictive value, negative predictive value and ROC (Receiver Operating Characteristic) curve. RESULTS: compared to ultrasound, the Capurro method overestimated the gestational age in newbornsof less than 39 weeks and underestimated it in older newborns. Ultrasound underestimated gestational agein newborns with more than 37 weeks. CONCLUSION: ultrasound was found to have greater sensitivity for prediction of small for age newborns (96.6%), while the Capurro method presented greater specificity (75.5%). The highest accuracy was obtained using ultrasound in the 41st gestational week (ROC=77.0%).